Skin Cancer in Albinos' Patients - Ahmad, Khadeejah Abdalsalam (faculty of Basic Medical Science - Libyan International Medical University, 2020)
Skin cancer among Africans is rare, and albinism in this population is a known risk of skin cancer. There are two main types of albinism which are ocular albinism and oculocutaneous albinism. Ultraviolet radiation at the equator is highest, and African albinos living near the equator are at greatest risk of developing skin cancer. In this report, the data are collected from the 2 published articles. The first study recorded of albinos administered into Imo State University Hospital from June 2007 to May 2009 were reviewed. The data obtained were analyzed using descriptive statistics. Second research is a retrospective review of all albinos with histological diagnosis of skin malignancies reported to Irrua Specialist Teaching Hospital, Irrua Edo State, Nigeria between September 2010 and August 2016. The following details were extracted from the patient casenotes. The result of most of the patients was under 55 years of age, the average duration of symptoms at diagnosis was approximately 26 months and squamous cell carcinoma was the most common histological type
Albinism is an inheritable disorder that affects the melanin production due to the absence or defect in tyrosinase enzyme which converts tyrosine to dioxyphenylalanine (the precursor of melanin) . 1 Mutations in tyrosinase (TYR) gene (11q14-q21), resulting in impaired tyrosinase activity, are by far the most common and affect up to 50% of cases worldwide . 3 This leads to the absence or reduction in melanin produced in the melanocytes which affect the skin, eyes, and hair